Utilization of the Problem-Based Learning (PBL) Model to Develop Critical Thinking Skills of Fourth-Grade Elementary School Students - Calosa, Aditya Bagas; Anggoro, Subuh; Suryani, Suryani (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to improve the critical thinking skills of fourth-grade elementary students through the implementation of the Problem Based Learning (PBL) model. Critical thinking is a vital 21st-century skill that must be nurtured from an early stage in education. Based on initial observations in Class IVB of SD Negeri 2 Purwokerto Wetan, it was found that most students were unable to express opinions, engage actively, or identify information effectively during thematic learning. Therefore, the PBL model was implemented in IPAS (Integrated Science and Social Studies) learning through two cycles of classroom action research (CAR). The research design followed the Kemmis and McTaggart model, including planning, action, observation, and reflection stages. Data were collected using observation, interviews, written tests, and documentation. The results showed a significant improvement in students' critical thinking skills after the application of PBL. In cycle I, the average critical thinking score was 70.3%, which increased to 84.1% in cycle II. Key aspects of critical thinking, such as providing basic explanations, making inferences, evaluating, and planning strategies, improved across most students. Additionally, the classroom atmosphere became more active, participatory, and collaborative, with more students able to present logical arguments and solve problems independently. The study concludes that the PBL model is an effective approach to enhancing elementary students' critical thinking abilities, especially in thematic IPAS learning.